Development of an analytical method to determine malondialdehyde as an oxidative marker in cryopreserved bovine semen - Yonny, Melisa Evangelina (2015)
Frozen sperm is widely used in artificial insemination of cattle as well as other animal species. As a consequence of the freezing and thawing processes of semen, an excess of reactive oxygen species (ROS) are formed. ROS produce oxidative damage in sperm cells affecting both motility and fertility. Malondialdehyde (MDA) is one of the most recognized biomarkers of an advanced oxidative status. MDA was analyzed after its condensation reaction with thiobarbituric acid (TBA); however, other molecules can also react with TBA. In order to determine specifically the MDA–TBA2 condensation product in cryopreserved bovine semen, a sensitive and selective separation strategy was developed using high performance liquid chromatography (HPLC) with diode array detection (DAD). This is the first report on MDA determination in bovine semen by a separation method. Different methodological approaches were assayed. Treatment A directly measured total MDA through acidic hydrolysis combined with TBA condensation in a single step. Treatment B evaluated separately the TBA condensation product of free MDA and protein bound MDA after its release with alkaline hydrolysis. The highest concentration of MDA was detected following treatment A. An HPLC method was developed and validated by comparing with the traditional spectrophotometric method. The detection and quantification limits were 0.034 μM and 0.086 μM. The DAD response was linear in the range between 0.086 and 9.1 μM. The recovery was 91%. The intra- and inter-day relative standard deviations were 3.7 and 3.8%, respectively. The proposed HPLC method was markedly more sensitive and more specific than the traditional spectrophotometric one.